The economic impact of caregiving for individuals with Angelman syndrome in the United States: results from a caregiver survey - John Jarvis; Elizabeth Chertavian; Marric Buessing; Taylor Renteria; Lufei Tu; Lauren Hoffer; Ryan Fischer; Amanda Moore; Meagan Cross; Megan Tones (Orphanet Journal of Rare Diseases)
Abstract Background Angelman syndrome (AS) is a rare neurogenetic disorder characterized by persistent cognitive and functional impairments that necessitate lifelong care. Caring for individuals with AS leads to substantial household costs, as well as impacts on work productivity, leisure time, and quality of life for caregivers. The economic value of these impacts in the United States (US) has not been well studied. We conducted a survey of US caregivers for persons with AS to quantify the annual economic impact of caregiving. Information on AS-related economic impacts was gathered, including household costs, employment impacts, leisure time loss, and caregiver healthcare costs. The survey did not gather information on direct medical care costs borne by healthcare insurers or other economic impacts to the US government and other stakeholders. Results A total of 105 caregivers completed the survey and 105 individuals with AS were represented. Most caregivers were female (89.5%), white (83.8%), and identified as the primary caregiver (75.2%). Most individuals with AS represented in the sample were age < 18 (82.9%). The annual economic impact of caregiving for persons with AS averaged $79,837 (SD $55,505). Costs related to employment impacts and lost work productivity in the past 12 months accounted for most (53%) of this impact and averaged $42,697 (SD $28,309). Household costs incurred in the past 12 months for goods and services to better accommodate individuals with AS were $29,680 (SD $47,753). Leading contributors included vehicle purchases and modifications (mean $6,717; SD $17,791), professional caregiving (mean $6,123; SD $17,335), home modifications and repairs (mean $4,387; SD $15,734), and supportive therapy (mean $3,269; SD $7,564). Economic impacts in the past 12 months from lost leisure time and incremental healthcare costs for caregivers were estimated to be $6,634 (SD $4,652) and $827 (SD $2,072), respectively. Conclusions Caregivers incur substantial costs to accommodate individuals with AS, as well as substantial impacts related to employment and leisure time. This study’s findings may be utilized in future research to better estimate the value from therapeutic advances in AS and direct resources toward mitigating economic impacts for households.